KKT OPTIMALITY CONDITIONS FOR INTERVAL VALUED OPTIMIZATION PROBLEMS - Singh, D.; Dar, B. A.; Goyal, A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2014)
In the present paper we study the class of convex optimization problems in uncertain environment. The objective and constraint functions are assumed to be interval valued. Solution concepts are proposed under two order relations on the set of all closed intervals. Weakly continuously differentiability is employed in order to derive necessary and sufficient conditions for KKT optimality conditions. These theoretical developments are illustrated through a numerical example